A caracterização física dos resíduos sólidos domiciliares de Fortaleza como fator determinante do seu potencial reciclável - Firmeza, Sérgio de Miranda (2005)
In this work, a physical characterization of solid home waste (garbage) in the city of Fortaleza was done, with the aim at getting to know the composition of solid waste, their respective percentuals and the rate of generation per capita. As a first step, a bibliographic review was done. After that, a visit at public institutions and interviews with technicians from the Empresa Municipal de Limpeza e Urbanização – EMLURB (cleaning and urbanization company of the city) were done, in order to obtain information about urban cleaning system and its management. Furthermore, it was made a field recognition with visits to all neighborhoods, considering the administrative division of the city, which covers the twenty five garbage generator zones and are part of the six regional executive secretaries, at the complex of Jangurussu (garbage sort and transference), at the place where garbage is buried, at rivers Ceará and Cocó estuaries and orle. The garbage flow (generation, collection, transportation and final destination) was watched. Finally, it was made a field survey, through which it was collected 792 samples of garbage produced in the permanent homes in all neighborhoods of Fortaleza, 2004, from april to december. As a result from the characterization of waste, it was identified the components and their respective percentuals in the twenty five garbage generator zones. Working with these data, it was possible to determine their average distribution in the six regional executive secretaries, as well as to identify areas with more recyclable material production, the per capita garbage production, the projection of the per capita home garbage and the per capita production of recyclable garbage. It was observed that the percentual of recyclable material is significant and it should be collected separatedly, through selective collect, in order to preserve their characteristics, aiming at recycling. The indicator found at garbage production per capita could also be used as an index of home waste production collected without being paid by the city administration. In the conclusion, were expressed the perspectives about recycling garbage, the relevance of the work concerning decision-take strategies in the management of solid waste, due to its contribution, bringing information, which can be the base to a policy for solid waste at Fortaleza, with the aim at recycling the garbage, under the approach of participative sustainable development and the Agenda 21, with advises and suggestions.